Feeding rats with used cooking oil elevates malondialdehyde, TNF-α, and creatinine compared to tempe fried with used oil - Murwani, Retno; Susilaningsih, Neni; Ariyanto, Diaza O.; Ambariyanto, Ambariyanto (Narra Sains Indonesia, 2024)
In vivo studies on the hazards of deep-fried foods were commonly done by feeding used- or heated-cooking oil to rats. The aim of this study was to determine the effect of feeding tempe deep-fried in palm, olive, and coconut oils and the used frying oil on the blood biochemical profile of laboratory rats. An in vivo randomized control group study with pre-test and post-test was conducted. This study included healthy male Sprague-Dawley rats aged 2–3 months and weighing 100−200 grams. After acclimatization, the rats were randomly assigned to seven groups, which were: (1) regular diet (control diet); (2) diet of tempe deep-fried in 5× used palm oil (Tempe-in-used-Po); (3) diet of tempe deep-fried in 5× used coconut oil (Tempe-in-used-Co); (4) diet of tempe deep-fried in 5× used olive oil (Tempe-in-used-Oo); (5) diet of 5× used palm oil (Used-Po); (6) diet of 5× used coconut oil (Used-Co); and (7) diet of 5× used olive oil (Used-Oo). Each rat received 15 grams of a treatment diet daily and blood samples were collected after four weeks for a complete blood count and serum biochemistry analysis. The results showed that the final body weight and the weight gain of Tempe-in-used-Po, Tempe-in-used-Co, Tempe-in-used-Oo group, and Used-Po groups increased significantly compared to the control, Used-Co, and Used-Oo groups. However, there was a significant increase in serum tumor necrosis factor-alpha (TNF-α) in the Used-Co and Used-Oo groups (p<0.05), suggesting the used oil's detrimental effect. The Used-Co and Used-Oo were the only two groups whose creatinine increased significantly (p<0.05). Subsequently, only the Used-Oo group had a significantly increased malondialdehyde (MDA) level compared to all groups (p<0.05). These results prove that the effect of feeding fried food differs from used oils. Feeding used oil did not reflect the consumption of fried foods as part of the whole diet and generally resulted in more harmful effects. This is the first study to report an in vivo rat feeding study of deep-fried tempe and the used oil as part of the diet.